Deskripsi Naratif dalam Kontekstualisasi Ayat-Ayat Al-Qur’an tentang Keadilan Sosial - Rahmatul Qadri; Bani Adam I’tishan; Supriadi; Amir Hamzah (Kartika: Jurnal Studi Keislaman, 2026)
Social justice remains a central concern in today’s global context, marked by persistent structural inequalities, imbalanced power relations, and the ongoing marginalization of vulnerable communities. Within Qur’anic studies, addressing this issue requires an interpretive framework that moves beyond purely normative or legalistic readings, toward an approach that engages the social and ethical dimensions embedded in the text. This article examines how the Qur’an’s narrative descriptions shape an understanding of social justice values and explores the ways in which these values can be meaningfully contextualized within contemporary social realities. Employing a qualitative descriptive method through library research and narrative analysis, this study focuses on Qur’anic verses that articulate themes of social justice. The findings reveal that the Qur’an’s narrative structure articulates social relationships, critiques systemic injustice, and emphasizes collective moral responsibility in a manner that transcends historical boundaries. When related to modern issues such as economic disparity, exploitation, and systemic oppression, these values demonstrate strong reflective and transformative potential. Consequently, this study contributes to the development of narrative-based approaches in Qur’anic scholarship and proposes a more accessible and contextually relevant model for interpreting verses on social justice in modern social discourse